2012
DOI: 10.1111/j.1749-8198.2011.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of International Education: Mobilities and the Reproduction of Social (Dis)advantage

Abstract: This paper provides a critical perspective on emergent geographies of international education, suggesting what these might mean for the reproduction of social (dis)advantage. The assertion that formal education may have regressive consequences for social mobility is hardly new – work on the sociology and geography of education has for a long time shown uncontrovertibly that the opportunities and rewards associated with formal education are unevenly distributed across space, as well as being differentiated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 99 publications
(228 reference statements)
1
115
0
2
Order By: Relevance
“…This is the way in which the glocalisation of student mobility is evident in the research that we have reported. While student migration is geographically embedded within social class reproduction and the formation of an educated elite across the four nations of the UK (King et al, 2011;Waters, 2012), it is equally true that the paper points to the importance that global forces have in the geographical organisation of higher education and in the student flows (internal and international) that result from this. In particular the paper has argued that while the search for distinction is a global process entwined in the complexities associated with the internationalisation of higher education, the outworking of this is not limited to international student flows.…”
Section: Discussion and Conclusion: In What Sense 'Distinctive'?mentioning
confidence: 99%
See 3 more Smart Citations
“…This is the way in which the glocalisation of student mobility is evident in the research that we have reported. While student migration is geographically embedded within social class reproduction and the formation of an educated elite across the four nations of the UK (King et al, 2011;Waters, 2012), it is equally true that the paper points to the importance that global forces have in the geographical organisation of higher education and in the student flows (internal and international) that result from this. In particular the paper has argued that while the search for distinction is a global process entwined in the complexities associated with the internationalisation of higher education, the outworking of this is not limited to international student flows.…”
Section: Discussion and Conclusion: In What Sense 'Distinctive'?mentioning
confidence: 99%
“…In summary, while there has been considerable work in recent years on international student mobility (Waters, 2012), intra-state flows have received less attention than one might expect from geographical researchers, especially given the significant divergence of the HE sectors in Scotland and England. In what follows, we argue that the patterning of internal student flows within the UK provides a useful empirical lens for studying the country's increasingly differentiated higher education market.…”
Section: The Changing Context Of Higher Education In the Ukmentioning
confidence: 99%
See 2 more Smart Citations
“…geographical scales, focusing on professionals in high-tech industries (e.g., Harvey, 2009;Saxenian, 2006;Van Riemsdijk, 2014) and advanced producer services (e.g., Beaverstock, 2005;Beaverstock & Hall, 2012;Fechter & Walsh, 2012;Walsh, 2012), on researchers and academics (e.g., Ackers, 2005;Heffernan & Jöns, 2013;Jöns, 2003;Leung, 2013;Pietsch, 2013;Storme, Faulconbridge, Beaverstock, Derudder, & Witlox, 2016), and on international students (e.g., Alberts & Hazen, 2013;Brooks & Waters, 2011;Findlay, King, Smith, Geddes, & Skeldon, 2012;Geddie, 2015;Holloway, O'Hara, & Pimlott-Wilson, 2012;King & Raghuram, 2013;Madge, Raghuram, & Noxolo, 2015;Waters, 2012).…”
mentioning
confidence: 99%